KEANEKARAGAMAN LEGUM LOKAL DI BUTON SELATAN - Yenni B; S Hafidhawati Andarias; Agus Slamet (Media Agribisnis, 2020)
Local legum is one of the important genetic resource materials. In South Buton, there are various types of local legum, whether cultivated or growing wild. The lack of local legum information motivation more exploration to investigate plant diversity characteristics.This study to collect data on local legum germplasm in South Buton and pre-identification potential genetic for legum breeding and their use as a functional food. Collections of morphological samples (flowers, pods, and seeds) were carried out using the exploratory method. The results of the study showed that 11 samples of local legum gene plasma were collected, based on the morphological character of local legum showed variation in flower color, pod characteristic (pod shape, pod color, and pod texture), and seed characteristics (shape and color of seed) also agronomy characteristic (the number of seeds, weight of seeds, age of planting and age of harvesting). The diversity of local legums can be used as a source of genes and alternative functional food in the future. Keywords: local legum, South Buton, diversity